2017
DOI: 10.1002/cam4.1088
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for high‐frequency microsatellite instability in colorectal cancer patients over 50 years of age

Abstract: Microsatellite instability (MSI) is an important biomarker for screening for Lynch syndrome, and also of response to immune checkpoint inhibitors. The aim of this study is to create a predictive model to determine which elderly patients with colorectal cancer (CRC) should undergo MSI and/or immunohistochemistry testing on the basis of clinicopathological data. We analyzed a test cohort of CRC patients aged ≥50 years (n = 2219) by multivariate logistic regression analyses to identify predictors of high‐frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…MSS is the case when no markers are unstable. We follow Fujiyoshi et al, 2017 study definition of MSI that was approved for Bethesda [2], [22]. In Fujiyoshi et al, 2017 study, they include MSI-L as MSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSS is the case when no markers are unstable. We follow Fujiyoshi et al, 2017 study definition of MSI that was approved for Bethesda [2], [22]. In Fujiyoshi et al, 2017 study, they include MSI-L as MSS.…”
Section: Methodsmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the most commonly observed cancer worldwide [1]. It is one of the most common cause of cancer-related death worldwide [2]. Cancer colon, as any cancer is caused by environmental and genetic factors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors targeting the programmed cell death-ligand 1 (PD-L1) and programmed cell death-1 (PD-1) pathway have shown durable responses in patients with microsatellite instability high (MSI-H) metastatic colorectal cancer (mCRC), a population that constitutes 3-5% of patients with mCRC. [1][2][3] In contrast, anti-PD-1/PD-L1 antibodies have little clinical benefit in patients with microsatellite-stable (MSS) mCRC. 1,4,5 Although most patients with MSS mCRC do not have T-cell infiltration and are considered the so-called "cold tumors", 6 the mechanism underlying immune resistance in such tumors remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that MMR status of CRC is significantly correlated with their clinicopathological features [ 17 , 18 ] and serum tumour biomarkers (STMs) [ 19 , 20 ]. Though several prediction models based on pathological features have been developed, the complex pathological characteristics included in previous models required detailed pathological diagnosis [ [21] , [22] , [23] ], which not only caused a huge burden on the pathologists, but also lacked of instructive value for clinicians. STMs are both important prognostic factors and the indicators of therapeutic effect and recurrence in patients with CRC [ 19 , 24 ], whereas their predictive value for MMR status has not been assessed in previous studies.…”
Section: Introductionmentioning
confidence: 99%